Anandamide Induces Platelet Nitric Oxide Synthase through AMP‐Activated Protein Kinase. Issue 9 (21st November 2018) - Signorello, Maria Grazia; Leoncini, Giuliana
Abstract: The objective of this study was to determine whether adenosine 5′ monophosphate (AMP)‐activated protein kinase (AMPK) is activated by anandamide (AEA) and is involved in endothelial nitric oxide synthase (eNOS) activation. We found that AEA stimulates and activates AMPKα through a Ca 2+ ‐dependent/Calmodulin (CaM)‐dependent pathway as the specific inhibitor of the Ca 2+ /Calmodulin kinase kinase β (CaMKKβ) STO‐609 abolishes the AMPK phosphorylation/activation. The same inhibiting effect is shown in platelets pretreated with LY294002, an inhibitor of phosphatidylinositol 3 kinase (PI3K), or with MK2206, an inhibitor of protein kinase B (AKT), suggesting that AMPK is downstream of the PI3K/AKT pathway. Moreover, the AEA‐induced eNOS activation and the consequent nitric oxide (NO) and guanosine 3′‐5′ cyclic monophosphate (cGMP) increase are mediated by the CaMKKβ/AMPKα pathway as STO‐609 significantly inhibits these parameters. In contrast, liver kinase B1 (LKB1) seems to be very poorly involved. One crucial effect of NO and cGMP elevation is the activation of protein kinase G that can phosphorylate the vasodilator‐stimulated phosphoprotein (VASP). We have demonstrated that AEA stimulates VASP phosphorylation on both thr278 and ser239 that is strongly inhibited by STO‐609, LY294002, and MK2206. Finally, AMPK phosphorylation/activation and VASP phosphorylation are significantly reduced by SR141716, the specific inhibitor of type 1 cannabinoid receptor (CB1). SR144528, an antagonist of type 2 cannabinoid receptor (CB2), has a less‐potent effect, suggesting that the CB1 receptor is overall involved in the AEA effect. In conclusion, we show that the CaMKKβ/AMPKα pathway, downstream of the PI3K/AKT pathway, is activated by AEA in human platelets and leads to increase NO levels producing beneficial effects during ischemic conditions and contributing to extend platelet survival.